The answer to this question that you have me would be 5|x|-7=7 will equal to x=2
Answer:
Step-by-step explanation:
Question (1)
x² + 10x + 12
= x² + 2(5x) + 5² - 5² + 12
= [x² + 2(5x) + 5²] - 5² + 12
= (x + 5)² - 25 + 12 [Since, a² + 2ab + b² = (a + b)²]
= (x + 5)² - 13
Question (2)
y² - 6y - 15
= y² - 2(3y) - 15
= y² - 2(3y) + 3² - 3² - 15
= [y² - 2(3y) + 3²] - 3² - 15 [Since, a² - 2ab + b² = (a - b)²]
= (y - 3)² - 3²- 15
= (y - 3)² - 9 - 15
= (y - 3)² - 24
Answer:
7x - 8.
Step-by-step explanation:
sad face
Slope of function B is "rising" 3 and going over to the right by 1. Representing the slope as 3/1 = 3.
Slope of function A is already giving. If you multiply the slope of function B by 2, it will equal the slope of Function A